2018
DOI: 10.1002/anie.201807741
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscopic Visualization of Cross‐Linking Density in Polymer Networks with Diarylethene Photoswitches

Abstract: The in situ nanoscopic imaging of soft matter polymer structures is of importance to gain knowledge of the relationship between structure, properties, and functionality on the nanoscopic scale. Cross-linking of polymer chains effects the viscoelastic properties of gels. The correlation of mechanical properties with the distribution and amount of cross-linkers is relevant for applications and for a detailed understanding of polymers on the molecular scale. We introduce a super-resolution fluorescence-microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 69 publications
1
71
0
1
Order By: Relevance
“…Very recently, the presence of higher crosslink density clusters within a PNIPAM microgel was shown in real space using high resolution fluorescence microscopy and dye tagging. 64,65 Thus, according to these results, we conclude that domains remain at 50 1C even at higher crosslinker concentration. Moreover, the estimation of the domain number within one particle also confirms this assumption.…”
Section: 2supporting
confidence: 71%
“…Very recently, the presence of higher crosslink density clusters within a PNIPAM microgel was shown in real space using high resolution fluorescence microscopy and dye tagging. 64,65 Thus, according to these results, we conclude that domains remain at 50 1C even at higher crosslinker concentration. Moreover, the estimation of the domain number within one particle also confirms this assumption.…”
Section: 2supporting
confidence: 71%
“…Previous studies revealed that diarylethenes can be activated using lasers with longer wavelengths due to the presence of Urbach tails, therefore, a single laser (532 nm) was used for activation, excitation and deactivation. 14,15,[45][46][47] Compared to diffraction-limited uorescent images (Fig. 2a), SMLM images are much clearer and provide more information regarding the local distribution of uorophores (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The fuzzy shell is found to shrink first, while the core is only compressed for ζ 0.8. This can be understood from the fact that the polymer density decreases towards the particle periphery [18,25]. Hence, the particle outskirts are expected to be the softest part of the particle and that is why it is compressed first.…”
Section: Prior Results: Deswelling At High ζmentioning
confidence: 99%
“…Because the crosslinker reacts faster than the NIPAM monomer during synthesis, the microgels have a coreshell structure, with a shell whose polymer density decays from the compact core towards the periphery [18,24,25]. Their structure is, therefore, modeled by a spherical core with radius R core and homogenous density that is convoluted with a Gaussian to obtain a shell with decreasing polymer density.…”
Section: Microgel Suspensionsmentioning
confidence: 99%